Association between fecal egg count and weight gain in young beef cattle - Zapa, Dina María Beltrán; Couto, Luiz Fellipe Monteiro; Heller, Luciana Maffini; Cavalcante, Alliny Souza de Assis; Nicaretta, João Eduardo; Cruvinel, Leonardo Bueno; Maciel, Willian Giquelin [UNESP]; Teixeira, Weslen Fabricio Pires; Felippelli, Gustavo [UNESP]; Gomes, Lucas Vinicius Costa [UNESP]; Ferreira, Lorena Lopes; Soares, Vando Edesio; et al. (Elsevier, 2021)
Gastrointestinal helminths are a problem in the production of ruminants, parasitized animals show delayed growth. The present study evaluated the association between fecal egg count (FEC), done using a modified McMaster technique, and weight gain of 41,837 naturally infected male and female Nellore and crossbred beef cattle — in three categories: nursing beef calves, weaned calves with supplementary protein diet and weaned calves without supplementary protein diet — over a 30-day period during the rainy season. Cooperia (64.5%) was the most frequent genus parasitizing the animals. A reduction in weight gain occurred for nursing calves when eggs per gram (EPG) was ≥ 500 to 2,750 (-5.5 to -12.9 kg, respectively), in comparison to calves with FEC = 0. A reduction in weight gain for non-supplemented weaned calves occurred with EPG ≥ 12.5 to 3,550 (-1.6 to -7.1 kg, respectively) in comparison to calves with FEC = 0. In contrast, weight gain was approximately 15 kg for supplemented weaned calves with EPG between 500 and 1,700. A negative correlation was found between EPG and weight gain for non-supplemented weaned crossbred animals (R² = 0.7565; r = - 0.8698; P = 0.0001) and for nursing calves with EPG value ≥ 500 (R² = 0.7564; r = - 0.87; P = 0.0023). There was also a negative correlation, but not very strong, between EPG and weight gain for non-supplemented weaned Nellore calves (R² = 0.4493; r = - 0.6703; P = 0.0122), whereas these two variables were positively correlated over the 30-day period for protein-supplemented weaned Nellore calves (R² = 0.7229; r = 0.85; P = 0.0036). Moreover, non-supplemented weaned crossbred calves exhibited greater weight gain compared to non-supplemented weaned Nellore calves when EPG was equal to zero. However, when these animals were naturally challenged with gastrointestinal strongyles, the Nellore calves proved to be more resilient than the crossbred animals. Protein supplementation could help maintain the resilience of yearling Nellore females when affected by helminth parasitism.
Keywords: Beef herd; Cooperia; EPG; Gastrointestinal helminths; Strongyles